2018
DOI: 10.1016/j.bbalip.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ceramides and tear lipocalin

Abstract: The distribution of lipids in tears is critical to their function. Lipids in human tears may retard evaporation by forming a surface barrier at the air interface. Lipids complexed with the major lipid binding protein in tears, tear lipocalin, reside in the bulk (aqueous) and may have functions unrelated to the surface. Many new lipids species have been revealed through recent mass spectrometric studies. Their association with lipid binding proteins has not been studied. Squalene, (O-acyl) omega-hydroxy fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 88 publications
(119 reference statements)
3
16
0
Order By: Relevance
“…Fractionations of proteins, including tears, synthetic dimers and ligand binding complexes, were performed by gel filtration liquid chromatography using the AKTA purifier Versatile FPLC with a HiLoad Superdex 75 column (GE Healthcare, Piscataway, NJ). In general, one ml column fractions were collected with elution in 50 mM Tris-HCl, 100 mM NaCl pH 8.4 run at 1 ml/min as previously described [37]. For purification of tear lipocalin monomers peak fractions from gel filtration of 1 ml of tears were pooled and applied to an anion exchange column using DEAE-Sephadex A-25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractionations of proteins, including tears, synthetic dimers and ligand binding complexes, were performed by gel filtration liquid chromatography using the AKTA purifier Versatile FPLC with a HiLoad Superdex 75 column (GE Healthcare, Piscataway, NJ). In general, one ml column fractions were collected with elution in 50 mM Tris-HCl, 100 mM NaCl pH 8.4 run at 1 ml/min as previously described [37]. For purification of tear lipocalin monomers peak fractions from gel filtration of 1 ml of tears were pooled and applied to an anion exchange column using DEAE-Sephadex A-25.…”
Section: Methodsmentioning
confidence: 99%
“…Redl et al calculated 0.3 for the ratio of retinol to tear lipocalin at saturation [21]. A recent study with ceramide revealed stoichiometric ratios of TL:ceramide ligand from n = 0.32–0.67, accompanied by a very low dissociation constant [37]. Several explanations are possible including the formation of a multimeric complex with 2 lipocalin molecules flanking the 2 alkyl chains of the ceramide or a binding site pre-occupied by other ligands.…”
Section: Introductionmentioning
confidence: 99%
“…A thin layer of lipid1,2 on the tear film surface could influence the stability of tears 38. Most of the tear film lipid (TFL) comes from meibomian gland, but other sources such as sebaceous9 and lacrimal glands10 could contribute a minor portion of lipid to the TFL layer. Relationships between TFL layer composition, structure, and function could provide insight into the etiology of dry eye.…”
mentioning
confidence: 99%
“…Concomitantly, there is a rise in fluorescence at about 530 nm, which is the emission peak of C6-ceramide when protein bound [13]. The tear lipocalin dimer mirrors the ceramide binding function of the monomer to bind lipid in the calyx.…”
Section: Methods Validationmentioning
confidence: 99%